How Politics and Institutions Affect Pension Reform in Three Postcommunist Countries - Orenstein, Mitchell A. (World Bank, Washington, DC, 2015)
The author examines the political and institutional processes that produced fundamental pension reform in three post-communist countries: Hungary, Kazakhstan, and Poland. He tests various hypothesis about the relationship between deliberative process and outcomes through detailed case studies of pension reform. The outcomes of reform were similar: each country implemented a mandatory funded pension system as part of reform, but the extent, and configuration of changes, greatly differed. Countries with more veto actors - social and institutional actors with an effective veto over reform - engaged in less radical reform, as theory predicted. Poland and Hungary generated less radical change than Kazakhstan, partly because they have more representative political systems, to which more associations, interest groups, and proposal actors have access. Proposal actors shape the reform agenda and influence the positions of key veto actors. Pension reform takes longer in countries with more veto and proposal actors, such as Poland and Hungary. Legacies of policy, the development of civil society, and international organizations, also profoundly affect the shape and progress of reform. The author sees pension reform as happening in three phases: commitment-building, coalition-building, and implementation. He presents hypothesis about tradeoffs among inclusiveness (of process), radicalism (of reform), and participation in, and compliance with, the new system. The hypothesis: including more, and more various, veto and proposal actors early in the deliberative process, increases buy-in and compliance when reform is implemented, but at the expense of faster and greater change. Early challenges in implementation in all three countries, nut especially in Kazakhstan, suggest the importance of improving buy-in through inclusive deliberative processes, where possible.